Respostas

A melhor resposta!
2013-11-20T19:02:49-02:00
X²=y

y²-17y+16=0

Por báskara

289-4.(1).(16)
289-64
225

17+-15/2
y'= 32/2  =>   y': 16
y"" = 2/2  =>  y""=1

Substituindo:

x²=y'  =>   x² = 16  ->  x= +4 ou -4
x²= y""  => y""= +1 ou -1

S{ -4; -1; 1 ; 4}

Abraço! 


2 5 2
2013-11-20T19:04:38-02:00
Y² = 17y + 16 = 0
∆ = 289 - 64 
√∆ = 225
√∆ = 15

y = 17 ± 15 / 2
y' = 17 + 15 = 32 / 2 = 16
y'' = 17 - 15 = 2 / 2 = 1

y = 1 => x² = 1 => x = 
± 1
y = 16 => x² = 16 => x = ± 4

V = { +1; -1; +4; -4}

Abraços.